Regulatory Factor X1 Downregulation Contributes to Monocyte Chemoattractant Protein-1 Overexpression in CD14+ Monocytes via Epigenetic Mechanisms in Coronary Heart Disease - Jia, Sujie; Yang, Shuang; Du, Pei; Gao, Keqin; Cao, Yu; Yao, Baige; Guo, Ren; Zhao, Ming (Frontiers in Genetics, 2019)
Monocyte chemoattractant protein 1 (MCP1) affects the chemotaxis of monocytes and is a key chemokine closely related to the development of atherosclerosis (AS). Compared with healthy controls, coronary heart disease (CAD) patients show significantly upregulated plasma concentrations and mRNA expression of MCP1 in CD14+ monocytes. However, the specific regulatory mechanism of MCP1 overexpression in AS is still unclear. Our previous research indicated that there was no significant difference in the H3K4 and H3K27 tri-methylation of the MCP1 promoter in CD14+ monocytes from CAD versus non-CAD patients, but the H3 and H4 acetylation of the MCP1 promoter was increased in CD14+ monocytes from CAD patients. We further found that the H3K9 tri-methylation of the MCP1 promoter in CD14+ monocytes from CAD patients was decreased, but the DNA methylation levels did not differ markedly from those in non-CAD patients. Our previous work showed that the level of regulatory factor X1 (RFX1) was markedly reduced in CD14+ monocytes from CAD patients and played an important role in the progression of AS by regulating epigenetic modification. In this study, we investigated whether RFX1 and epigenetic modifications mediated by RFX1 contribute to the overexpression of MCP-1 in activated monocytes in CAD patients. We found that the enrichment of RFX1, histone deacetylase 1 (HDAC1), and suppressor of variegation 3-9 homolog 1 (SUV39H1) in the MCP1 gene promoter region were decreased in CD14+ monocytes from CAD patients and in healthy CD14+ monocytes treated with LDL (low-density lipoprotein). Chromatin immunoprecipitation (ChIP) assays identified MCP1 as a target gene of RFX1. Overexpression of RFX1 increased the recruitments of HDAC1 and SUV39H1 and inhibited the expression of MCP1 in CD14+ monocytes. In contrast, knockdown of RFX1 in CD14+ monocytes reduced the recruitments of HDAC1 and SUV39H1 in the MCP1 promoter region, thereby facilitating H3 and H4 acetylation and H3K9 tri-methylation in this region. In conclusion, our results indicated that RFX1 expression deficiency in CD14+ monocytes from CAD patients contributed to MCP1 overexpression via a deficient of recruitments of HDAC1 and SUV39H1 in the MCP1 promoter, which highlighted the vital role of RFX1 in the pathogenesis of CAD.